Examining the social participation of children and adolescents with Intellectual Disabilities and Autism Spectrum Disorder in relation to peers. Issue 5 (May 2016) - Taheri, A.; Perry, A.; Minnes, P.
Abstract: Background: Participation in social and physical activities has a number of benefits for children with or without disabilities. However, individuals with disabilities are often excluded from taking part in social activities. Most of the research on activity participation has focused on adults or youth with milder disabilities. However, children and adolescents with severe and complex needs, including those with autism, are often excluded from this type of research because of their complexities and level of functioning. Thus, we examined the social participation and friendships of children and adolescents with severe developmental disabilities, with and without autism, compared with peers without developmental disabilities. Methods: We compared the activity participation and friendships of typically developing children ( n = 210), children with an intellectual disability (ID only; n = 186), and children with autism spectrum disorder plus intellectual disability (ID + ASD; n = 232) between the ages of 3 and 19 years. Parents of these children completed a survey, which included questions about their children's participation in six activities, and the number and quality of their children's friendships. Results: Children and adolescents with ID only and ID + ASD were reported to participate in significantly fewer activities and to participate much less frequently than typically developing peers. Those with ID only and ID + ASD were reported to have fewer friends and poorer quality of friendships. In addition, those with ID + ASD participated even less frequently in some activities and had fewer friends relative to those with ID only. Conclusion: It is important to find ways to increase the social and activity participation of children and adolescents with ID only and ID + ASD. Future research should examine the barriers to such participation and factors that impact social participation in this population.